The Association Between Women's Perception of Birth During the Pandemic, Companion of Choice and Support From Health Professionals: A Cross-Sectional Study in 20 Countries in the WHO European Region - Batram-Zantvoort, Stephanie; Miani, Céline; Mariani, Ilaria; Valente, Emanuelle Pessa; Zaigham, Mehreen; Kolokotroni, Ourania; Sarantaki, Antigone; Baranowska, Barbara; Abderhalden-Zellweger, Alessia; de La Rochebrochard, Elise; Otelea, Marina Ruxandra; Liepinaitienė, Alina; et al. (My University, 2025)
Mitigation measures implemented in response to the COVID-19 pandemic led to significant changes in maternity care across Europe, including restrictions on companions during labor and birth. This cross-sectional study explores the association between the presence of a companion of choice and a positive perception of the birth experience. Additionally, it explores the association between health professionals' attention, assistance, and availability during labor and birth and a positive perception of birth.
Keywords: COVID‐19; WHO standards; companion of choice; disrespect and abuse; maternal experiences; positive birth perception; respectful maternity care